Ponseti Method of Correction of Congenital Talipes Equinovarus Deformity Under Two Year of Age Using Dimeglio Scoring System - Muhammad Khurram Habib; Ahmad Humayun Sarfraz; Syed Faraz Ul Hassan Shah Gillani; Faisal Masood; Zeeshan Ali Khan (Annals of King Edward Medical University, 2019)
Background: Congenital talipes equinovarus (CTEV) is the most common disorder of foot. Conservative treatment is the first line management for CTEV. Our objective was to determine the frequency of successful outcome of non-surgical correction of CTEV deformity between 6month to 2year age using Dimeglio scoring system. Method: This multicenter descriptive case series was done using non-probaility consecutive sampling technique. Total 62 cases, having age of 06 months to 02-year, of both genders, with failed conservative treatment of clubfoot diagnosed on history and clinical examination were enrolled. They were treated with six ponseti cast at one-week interval. Cast was removed in out patient department and after manipulation new cast was applied. The last cast was applied for two weeks. Patients were followed up at two weeks, one month, three months and after six months. We recored findings at six months only. Results: There were 43 males (69.4%) and 19 females (30.6%). Mean age was 11.16±5.52 months. Frequency of outcome results was excellent in 30 patients (48.4%), good in 20 patients (32.3%), fair in 08 patients (12.9%) and poor in 04 (6.5%). Frequency of successful surgical correction of CTEV with posteromedial soft tissue release is 50 (80.6%). Statistically significant difference was found between ages of children and hind foot varus (p<0.05) and between ages of children and ankle dorsiflexion. Conclusion: There were more male population than female in our study. The radiological outcome was excellent to good in majority of the patients treated with ponseti cast with minimum failed treatment.